Somatic symptom disorder with predominant pain: a case report (Bangladesh Journal of Psychiatry, 2021)
Somatic symptom disorder with predominant pain is a condition where there is preoccupation with pain without any organic pathology. This was a case report of 48 years old woman who had been suffering from severe pain and multiple suicidal attempts for a long time. Detailed physical examination and relevant investigation revealed no organic abnormality. She was diagnosed as somatic symptom disorder with predominant pain. Both diagnosis and management were challenging because of her poor responsiveness to previous treatment. She was partially improved with combination of pharmacotherapy and psychotherapy.Bang J Psychiatry 2021;35(2): 39-41